2014
DOI: 10.2208/journalofjsce.2.1_285
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Shear Behavior of PBL Joint Connections for Ufc-Pc Hybrid Girder

Abstract: The experimental results and predictive equation for shear capacity of Perfobond strip (PBL) joint connection with cast-in-place UFC to develop UFC-PC hybrid girders are presented in this paper. The UFC-PC bridge consists of PC segment at both ends and UFC segment at the middle of the span. Push-out test of twelve specimens was conducted. The experimental parameters were thickness of PBL, diameter of the hole of PBL, diameter of transverse rebar, prestressing stress on connection part, and the ratio of spacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For this reason, initial cracking may develop at the steel/concrete interface when RPC is utilized. Additionally, the interfacial restrains at the steel plate/concrete interface is beneficial in enhancing the shear capacity of PBL [23][24][25][26]. However, the shrinkage of RPC may decrease the confinement effects from the steel cells and results in a drop of PBL resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, initial cracking may develop at the steel/concrete interface when RPC is utilized. Additionally, the interfacial restrains at the steel plate/concrete interface is beneficial in enhancing the shear capacity of PBL [23][24][25][26]. However, the shrinkage of RPC may decrease the confinement effects from the steel cells and results in a drop of PBL resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the shear capacity of PBL in superimposed beams was improved by increasing the strength of UHPC. Wirojjanapirom et al [26] investigated the efficiency of using UHPC to improve the shear capacity of PBL by twelve prestressed short-beam tests. Results of the study showed an increase of PBL shear capacity due to the application of pre-stressing force.…”
Section: Introductionmentioning
confidence: 99%